2019
DOI: 10.1093/schbul/sbz015
|View full text |Cite
|
Sign up to set email alerts
|

Increased and Decreased Superficial White Matter Structural Connectivity in Schizophrenia and Bipolar Disorder

Abstract: Schizophrenia (SZ) and bipolar disorder (BD) are often conceptualized as “disconnection syndromes,” with substantial evidence of abnormalities in deep white matter tracts, forming the substrates of long-range connectivity, seen in both disorders. However, the study of superficial white matter (SWM) U-shaped short-range tracts remained challenging until recently, although findings from postmortem studies suggest they are likely integral components of SZ and BD neuropathology. This diffusion weighted imaging (DW… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 88 publications
1
26
0
2
Order By: Relevance
“…In addition, although we found "widespread" WM abnormalities in patients with BD, the robust ENIGMA DTI pipeline used to partition the ROIs involved only long and isolinear bundles. With this methodological approach (i.e., FSL TBSS), we cannot evaluate localized changes within the superficial WM, as have been previously observed in BD and schizophrenia [43]. Also, this methodological approach poorly reconstructs fiber crossings, which may have led to incomplete localization of group differences.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, although we found "widespread" WM abnormalities in patients with BD, the robust ENIGMA DTI pipeline used to partition the ROIs involved only long and isolinear bundles. With this methodological approach (i.e., FSL TBSS), we cannot evaluate localized changes within the superficial WM, as have been previously observed in BD and schizophrenia [43]. Also, this methodological approach poorly reconstructs fiber crossings, which may have led to incomplete localization of group differences.…”
Section: Discussionmentioning
confidence: 96%
“…Ellen et al found functional hyperconnectivity of the default mode network in SCH patients (75). Compared with BD patients, SCH patients exhibited decreased structural aggregation in the forehead region (76).…”
Section: Discussionmentioning
confidence: 99%
“…The microstate class C might be generated at the bilateral medial temporal gyrus and the lateral parietal lobe [32], which were found to be associated with self-experience in fMRI studies [41,42]. It was also considered that microstate class C was associated with the activation of the default mode network [16,35], the abnormal activation of which has been repeatedly demonstrated in schizophrenia [43,44]. Therefore, the increase of microstate class C might explain the abnormalities in self-focus and the self-experience in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%